Student occupational choices their influencing factors and development implications - Barrido, Leticia P (Iloilo City University of the Philippines in the Visayas, 1981)
This study aimed to find out the occupational choices of the National High school students in the Province of Iloilo. Specifically, it attempted to answer the following questions: 1. What are the occupations preferred most by the National High School senior students? 2. What are the alternative occupations of these students? 3. What factors affect the occupational choices of these students? 4. What are the implications of these occupational choices to the objectives of the Provincial Development Plan? The study was limited to the survey of occupational choices of the senior students in the ten National High schools in the Province of Iloilo, namely : Alimodian National Comprehensive High School, Barotac Nuevo National Comprehensive High School, Barotac Viejo National High School, Cabatuan National Comprehensive High School, Duenas National comprehensive High School, Janiuay National Comprehensive High School, Sta. Barbara national Comprehensive High School, San Enrique National Comprehensive High School, and Ajuy National Comprehensive High School. It was further limited to the relationship between the occupational choices of the students and the existing manpower needs of the Province. The study principally utilized both descriptive and normative treatment of the data gathered. The occupational choices of the students were influenced by several factors: interest, socio-cultural and economic background, parental influence, financial and job opportunities, service to society, expressed interest and personal desire, There were no statistically significant relationship between the respondents' occupational choices and the manpower needs of the Province. The occupational choices of the students did not fulfill the objectives of the Provincial development Plan.
[Research Paper] (Master of Education). -- [Iloilo City] : U.P. in the Visayas-CAS, April 1981.